Monitoramento da Estabilidade Oxidativa no Armazenamento de Biodiesel Metílico de Soja/Mamona e Blendas em Recipientes de Vidro - Melo, Marco Aurelio Rodrigues de (2009)
The present paper aimed at synthesizing, storing and monitoring biodiesel from the alkaline homogeneous transesterification of soybean oil and castor oil, using the methanol route, as well as evaluating the oxidative stability, during a 60 day-period, by means of the EN14112 standard. Blends of castor oil biodiesel and soybean oil biodiesel, containing 10, 20 and 30% v/v of castor oil biodiesel, respectively called M10, M20 and M30, were stored within illuminated and closed glass containers and later characterized. The physico-chemical analyses, performed for the two different biodiesel types and their blends, met most the requirements stated by the Technical Rule number 7 from the Brazilian National Agency for Petroleum, Natural Gas and Biofuels. The exceptions were the oxidative induction time (0.60 h) and the kinematic viscosity (13.98 mm2/s), which displayed values outside the limits established by the aforementioned agency. The blends displayed a higher oxidative stability than the pure soybean oil biodiesel, obtained by the methanol route. Thus, the blends with higher amounts of castor oil biodiesel, obtained by the methanol route, presented a higher safety, on the storage standpoint. The fluid-dynamic properties, cloud point, pour point and cold filter plugging point, pointed out similar behaviors for the blends and the pure biodiesels, obtained by the methanol route. Thus, in the studied concentrations, the castor oil methanol biodiesel acts as a natural additive for the soybean methanol biodiesel. By means of the EN 14112 standard, it was observed that the blend M30 is the one that is the most immune to the oxidation process, during the storage period of 60 days.